Controle genético da resistência a Meloidogyne incognita em Cucumis melo L - Candido, Willame dos Santos [UNESP] (2013)
This study was conducted at the College of Agriculture and Veterinary Sciences (UNESP-FCAV) in Jaboticabal-SP, in order to evaluate the mode of inheritance of resistance of melon 'Gaucho Round' to Meloidogyne incognita. Therefore, an experiment was conducted in randomized block design with three blocks and six treatments, which involved the parental lines 'Gaucho Round' (P1 resistant to M. incognita) and JAB 20 (P2 susceptible result of Breeding Program Culture Melon Tracery UNESP-FCAV), as well as the F1 (P1xP2), F2 (F1xF1) and backcross (RC1P1 and RC1P2). Individual plants were evaluated 70 days after inoculation with the pathogen through the nematode reproduction factor (FR), calculated by counting the number of eggs and second stage juveniles contained in the suspension of each root processed, divided by the initial population . The hypothesis of monogenic inheritance was rejected at a significance level of 1% probability in the chi-square (χ2), indicating that resistance is under the control of more than one gene locus, which was confirmed by quantitative analysis, which showed the existence of six genes involved in inheritance of resistance to nematodes. Predominance of additive effects in controlling the trait under study, allowing response to selection processes